The Effect of Bawang Dayak Tea on Sleep Quality in Patients With Type 2 Diabetes Mellitus - Annaas Budi Setyawan; U.S Mahadeva Rao (Journal Of Nursing Practice, 2026)
Background: Sleep disturbances are common among patients with Type 2 Diabetes Mellitus and are associated with poor metabolic control and reduced quality of life. Effective non-pharmacological and culturally relevant interventions are needed to improve sleep quality in this population. Purpose: This study aims to determine the effect of Bawang Dayak tea on sleep quality in patients with Type 2 Diabetes Mellitus. Methods: A quasi-experimental study with a pretest–posttest control group design was conducted in the working area of Community Health Center Wonorejo, Samarinda, from December 1 to 31, 2025. A total of 50 patients with Type 2 Diabetes Mellitus were assigned to an intervention group or a control group. The intervention received routine diabetes care and Bawang Dayak tea, while the control received routine care alone. Sleep quality was assessed before and after the intervention using a standardized sleep quality questionnaire. Data were analyzed using paired and unpaired statistical tests, with a significance level of < 0.05. Results: Paired analysis revealed a significant improvement in sleep quality in the intervention group following the intervention (p < 0.001), whereas the control group demonstrated a smaller but statistically significant change (p = 0.032). Unpaired analysis revealed that post-intervention sleep quality scores were significantly better in the intervention group compared with the control group (p < 0.001). Conclusion: Bawang Dayak tea significantly improves sleep quality in patients with Type 2 Diabetes Mellitus when used as a complementary intervention in diabetes care, supporting its potential integration into nursing practice for holistic diabetes.